Study on current climate change issues and response strategies - Li Jiayu; Tao Chongshuo; Zhang Yixian (E3S Web of Conferences)
Today, human activities are generating massive emissions of greenhouse gases, intensifying the issue of global climate change. This paper provides a comprehensive analysis of the current situation, impacts, and response strategies related to climate change. It also discusses the influences of climate change on agricultural production, socio-economic systems, and human health. Global warming, primarily caused by human-induced greenhouse gas emissions, has intensified due to feedback effects. Frequent extreme weather events and significant changes in ecosystems have profoundly affected agricultural production, socio-economic systems, and human health. To tackle climate change, mitigation and adaptation approaches are suggested, including the development of clean energy, ecosystem conservation, technological innovation, and policy support. It emphasizes the importance of international cooperation and points out that enhancing public education and participation is key to addressing climate change. In the future, global attention to and research on climate change must be continuously strengthened, and response strategies need to be constantly improved. Nations should further increase their investments in clean energy development, ecosystem protection, and technological innovation, faithfully fulfil international cooperation agreements, and jointly work to slow down the pace of climate change.